Exit or Voice? Behavioral Implications of Electoral-Integrity Beliefs in Germany - Christian Schnaudt (Politische Vierteljahresschrift, 2022)
Free and fair elections are the cornerstone of representative democracy. In recent years, however, elections in many advanced democracies have increasingly come under attack by populist actors and rhetoric questioning the integrity of the electoral process. While scholarly attention has so far largely focused on expert surveys measuring and documenting the objective integrity of different elections, a~thorough understanding of citizens' electoral-integrity beliefs and their implications for political behavior is still lacking. Against this background, the present study investigates the impact of electoral-integrity beliefs on citizens' political behavior in Germany. Specifically, the study aims to assess the influence of electoral-integrity perceptions on turnout, vote choice, and nonelectoral (institutionalized and noninstitutionalized) political participation in the offline and online spheres. The study's preregistered empirical analysis based on the preelection survey of the 2021 German Longitudinal Election Study shows that electoral-integrity beliefs entail clear implications for citizens' turnout and vote choice, while their influence on nonelectoral behavior is contingent upon the specific type and sphere of political participation. These findings provide novel insights on the behavioral implications of electoral-integrity beliefs and extend the (scarce) findings of previous research to (1)~a~broader political action repertoire as well as (2)~the German context. The empirical evidence generated comes with far-reaching implications for the general viability of modern democracies, suggesting that the nexus between electoral-integrity beliefs and political behavior can be a~"triple penalty" or a~"double corrective" for representative democracy.
Keywords: 320; Electoral fraud; Elections; Voting behavior; Political participation; Populism; Wahlbetrug; Wahlen; Wahlverhalten; Politische Partizipation; Populismus